Xanthogranulomatous Ureteritis Mimicking Ureteral Involvement by Cancer in a Radical Cystectomy Specimen. (May 2021) - Rodgers, Shannon A.; Williamson, Sean R.
Xanthogranulomatous pyelonephritis is well established as a renal mass-forming inflammatory process. However, a ureteral counterpart is minimally recognized. In this article, we present a case of xanthogranulomatous ureteritis in an 81-year-old woman, mimicking ureteral involvement by cancer in a radical cystectomy specimen for invasive urothelial carcinoma. Similar to the pathogenesis of xanthogranulomatous pyelonephritis, the patient was noted to have ureteral obstruction by calculus and had urine culture positive for Klebsiella pneumoniae . To our knowledge, this is the first report of xanthogranulomatous ureteritis associated with this pathogen and the only report associated with concurrent bladder cancer. Increased pathologist and urologist awareness of xanthogranulomatous ureteritis expands the spectrum of pseudotumoral processes of the ureter.